As relaç\~oes comerciais entre Brasil e Estados Unidos no período 2000-2014 - Uallace Moreira Lima (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The objective of this paper is to analyze the trade flow between Brazil and the United States between 2000 and 2014, considering its evolution and analyzing indicators such as export and import tariffs, relative importance of bilateral trade, trade intensity index, concentration index, index of comparative advantage revealed and the intersectoral pattern of bilateral trade. To contextualize the analysis of trade flows between the two countries, a brief retrospective of the conduct of Brazilian foreign policy between 2000 and 2014 is presented, particularly considering the strategies of Brazil's diplomatic relations with the United States, whose objective is to provide subsidies for construction hypotheses and speculations about the relationship between foreign policy and trade flows. In this sense, it is important to point out that no assertion is made in the sense that foreign policy has determined the behavior of trade flows between the two countries, since during the period there were several other factors operating and there is no analysis to capture the relevance of foreign policy.
Keywords: F1; F15; F5; 330; foreign policy; foreign trade; Brazil; United States